Effects of combined creatine plus fenugreek extract vs. creatine plus carbohydrate supplementation on resistance training adaptations - Taylor, L.; Poole, C.; Pena, E.; Lewing, M.; Kreider, R.; Foster, C.; Wilborn, C. (Journal of Sports Science & Medicine, 2011)
The purpose of this study was to evaluate the effects of combined creatine and fenugreek extract supplementation on strength and body composition. Forty- seven resistance trained men were matched according to body weight to ingest either 70 g of a dextrose placebo (PL), 5 g creatine/70 g of dextrose (CRD) or 3.5 g creatine/900 mg fenugreek extract (CRF) and participate in a 4-d/wk periodized resistance-training program for 8-weeks. At 0, 4, and 8-weeks, subjects were tested on body composition, muscular strength and endurance, and anaerobic capacity. Statistical analyses utilized a separate 3X3 (condition [PL vs. CRD vs. CRF] x time [T1 vs. T2 vs. T3]) ANOVAs with repeated measures for all criterion variables (p < 0.05). No group x time interaction effects or main effects (p > 0.05) were observed for any measures of body composition. CRF group showed significant increases in lean mass at T2 (p = 0.001) and T3 (p = 0.001). Bench press 1RM increased in PL group (p = 0.050) from T1-T3 and in CRD from T1-T2 (p = 0. 001) while remaining significant at T3 (p < 0.001). CRF group showed a significant increase in bench press 1RM from T1-T2 (p < 0.001), and also increased from T2-T3 (p = 0.032). Leg press 1RM significantly increased at all time points for PL, CRD, and CRF groups (p < 0.05). No additional between or within group changes were observed for any performance variables and serum clinical safety profiles (p > 0.05). In conclusion, creatine plus fenugreek extract supplementation had a significant impact on upper body strength and body composition as effectively as the combination of 5g of creatine with 70g of dextrose. Thus, the use of fenugreek with creatine supplementation may be an effective means for enhancing creatine uptake while eliminating the need for excessive amounts of simple carbohydrates.